THU0405 PREVALENCE OF FIBROMYALGIA IN INFLAMMATORY BOWEL DISEASE (IBD) PATIENTS: A SINGLE CENTRE OBSERVATIONAL PROSPECTIVE STUDY. (June 2019) - Tinazzi, Ilaria; Variola, Angela; Geccherle, Andrea; Marchetta, Antonio; Mcgonagle, Dennis
Abstract : Background: Joint pain is frequently reported by IBD patients and can be associated to extra-intestinal manifestations of diseases or adverse events associated to anti-TNF or vedolizumab therapy and also associated with other non-SpA-disease related factors including mechanical/degenerative problems. An appropriate rheumatological referral pathway is crucial to drive therapeutic strategy in case of concomitant spondyloarthritis (SpA). Fibromyalgia is a frequent cause of chronic pain that needs to be identified in order to not overestimate the prevalence of SpA in IBD patients Objectives: The aim of the study was to assess the prevalence of FM in a cohort of IBD outpatients Methods: Consecutive patients of the IBD Unit coming for a routine visit were screened by a rheumatologist in order to identify cases presenting the 2010 ACR criteria for FM or ASAS criteria for SpA (1, 2). Patients affected by other rheumatic conditions such as rheumatoid arthritis and crystal arthritis were excluded from the study. The rheumatological assessment included a 66 swollen joint count (SJC) and 68 TJC, MASEI, LEI and the fibromyalgia tender points examination. The patient completed BASDAI and BASFI on the day of clinical evaluation. Imaging exams (MSK ultrasound, MRI) and HLA-B27 determination were requested if needed for diagnostic confirmation Results: Between January to May 2018, 210 patients were enrolled in the study and 181 completed the clinical and imaging/laboratory assessment if requested for diagnostic purpose. examination. A total of 44 patients (24.3%) in the IBD cohort met the ACR 2010 criteria for FM. 34 patients (18.8%) presented the criteria for primary FM, and 10 patients (5.5%) presented FM and SpA. Of note FM patients presented LEI; BASDAI and BASFI scores higher than SpA patients Conclusion: FM is a common comorbidity in IBD patients and can be associated to SpA. An appropriate rheumatological referral is crucial exclude a concomitant SpA and to manage FM References: [1] Wolfe, et al. The American College of Rheumatology preliminary diagnostic criteria for fibromyalgia and measurement of symptom severity. Arthritis Care and Research. 2010;62(5):600–610. [2] Rudwaleit M, et al. The Assessment of SpondyloArthritis international Society classification criteria for peripheral spondyloarthritis and for spondyloarthritis in general. Ann Rheum Dis 2011;70:25–31 Disclosure of Interests: Ilaria Tinazzi: None declared, Angela Variola: None declared, Andrea Geccherle: None declared, Antonio Marchetta: None declared, Dennis McGonagle Consultant for: Lilly, Novartis UCB, Speakers bureau: Lilly, Novartis UCB